1992
DOI: 10.1210/endo.131.5.1425410
|View full text |Cite
|
Sign up to set email alerts
|

Role of luteinizing hormone in the expression of cholesterol side-chain cleavage cytochrome P450 and 3 beta-hydroxysteroid dehydrogenase, delta 5-4 isomerase messenger ribonucleic acids in the primate corpus luteum.

Abstract: It is well established that LH has an obligatory role in the acute production of progesterone by the primate corpus luteum in vivo because interruption of LH support to the corpus luteum at any time during the luteal phase is accompanied by an immediate and sustained fall in serum progesterone concentrations. However, recent studies have demonstrated that maximal steroidogenic capacity of cultured human luteal cells and maximal levels of messenger RNAs (mRNAs) for cholesterol side chain cleavage cytochrome P45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…7). This transcript size corresponded to the reported size for h3␤HSD in macaque CL (50,51). The message for 3␤HSD was also present in whole nonluteal ovary and in a CL obtained from a baboon treated with hCG to mimic early pregnancy.…”
Section: Resultssupporting
confidence: 76%
“…7). This transcript size corresponded to the reported size for h3␤HSD in macaque CL (50,51). The message for 3␤HSD was also present in whole nonluteal ovary and in a CL obtained from a baboon treated with hCG to mimic early pregnancy.…”
Section: Resultssupporting
confidence: 76%
“…1 illustrates serum progesterone concentrations in three monkeys during spontaneous luteal phases (shaded area) and in three monkeys that were treated with the GnRH antagonist for 7 days, beginning on day 8 of the luteal phase. As demonstrated previously (16,17), serum progesterone concentrations fell rapidly upon administration of GnRH antagonist and were undetectable 4-5 days after the initiation of treatment. Menses occurred on days 12-14 after ovulation in the GnRH antagonist-treated animals as compared with days 15, 16, and 19 in the spontaneously cycling animals.…”
supporting
confidence: 71%
“…Comparison of the AUCs of the individual treatment groups before the initiation of the gonadotropin infusions (days 0-7) revealed that the cumulative production rates of progesterone of the animals that subsequently were treated with the exponential infusion regimen of CG were, for unexplained reasons, greater than those of the other treatment and control groups, hence the extent to which the absolute amounts of progesterone seen in this group during gonadotropin treatment may have been biased by the elevated pretreatment values is uncertain. When the data from these animals were normalized to those that received the exponentially increasing LH regimen by multiplying the day [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] AUCs by the ratio of their cumulative progesterone levels observed during days 0-7 (i.e., day 0-7 LHe͞day 0-7 CGe), the resultant normalized values for the animals that received the exponentially increasing CG regimen (61.3 Ϯ 1.76) remained statistically greater than the animals that received the exponentially increasing LH regimen but were not statistically different from the pregnant animals.…”
Section: Physiology: Zeleznikmentioning
confidence: 99%
“…It is well established that administration of GnRH antagonist into monkeys during mid-luteal phase leads to suppression of LH secretion and abrupt termination of the luteal phase (Ravindranath et al, 1992;Duffy et al, 1999;Fraser et al, 1999). In the present study, Cetrorelix, a synthetic GnRH antagonist, was administered s.c., at a dose of 75 mg/kg body weight twice daily (09:00 and 21:00) on day 7 of the luteal phase of the menstrual cycle.…”
Section: Experiments I: Temporal Changes In Gene Expression During Gnrmentioning
confidence: 95%